Primary Splenic Pleomorphic Liposarcoma in a Bitch - Nascente, Eduardo de Paula; Adorno, Brunna Rocha; Santos, Adriana da Silva; Matos, Moema Pacheco Chediak; Porto, Regiani Nascimento Cagno; Santin, Ana Paula Iglesias; Moura, Veridiana Maria Brianezi Dignani de (Acta Scientiae Veterinariae, 2021)
Background: Liposarcoma is a malignant neoplasm of lipoblasts with low incidence in dogs, representing 1.7% of neoplasms diagnosed in the spleen. In veterinary medicine, this neoplasm is classified morphologically into the myxoid, well-differentiated, undifferentiated and pleomorphic subtypes, the latter being one of the most aggressive forms, mainly in cavity organs. This study reports a case of primary splenic pleomorphic liposarcoma in a female dog, addressing anatomopathological and immunohistochemical aspects. Case: A 14-year-old, 35 kg female mongrel canine with a history of absence of defecation, progressive weight loss, difficulty walking, sensitivity to abdominal palpation, prostration, pale mucous membranes, tachypnea and abdominal distention. The condition evolved to death and, on necroscopy, there was an increase in splenic volume with neoformation of whitish and reddish color, measuring 32 × 27 cm in its largest axes and weighing 8.9 kg. The neoformation exhibited areas of firm and soft consistency, and sectioning revealed the existence of focal areas of extensive necrosis and cavity collections of different diameters that allowed the flow of liquid serous contents with a brownish red color. Microscopy showed cells of neoplastic morphology infiltrating the splenic parenchyma, mostly with slightly acidophilic cytoplasm and few intracytoplasmic lipid vacuoles, which varied in size and distribution. The nuclei of the cells were large, eccentric and irregular, with round to oval morphology, grossly lacy chromatin and single or multiple evident nucleoli. These cells exhibited marked anisocytosis, anisokaryosis and pleomorphism, with more than one mitotic figure per high magnification field visible. Moderately inflammatory infiltrate, predominantly lymphocytic, permeated the neoplastic cells, and marked depletion of lymphoid follicles and atrophy of the red pulp were found in the remaining splenic parenchyma. Immunohistochemical tests revealed marked and discrete immunostaining for anti-vimentin and anti-S100 antibodies, respectively. No staining was observed for anti-pan cytokeratin, anti-desmin, anti-alpha smooth muscle actin or anti-CD20 antibodies. Based on anatomopathological and immunohistochemical aspects, it was concluded to be a splenic pleomorphic liposarcoma of primary origin. Discussion: the spleen is not a common anatomical site for the development of liposarcoma, a neoplasm whose origin remains unclear. Similar to what occurs in humans, liposarcoma is believed to develop from the adipose tissue of the splenic hilum. Thus, it should be considered as a differential diagnosis of invasive abdominal tumors. For the identification and classification of liposarcoma as a pleomorphic subtype, we considered mainly histological findings such as marked cell atypia and intracytoplasmic lipid vacuoles, which may or may not be present in neoplastic cells. Immunohistochemical examination favored the diagnosis of liposarcoma, regardless of the subtype, due to the marked immunostaining for the anti-vimentin antibody, unlike immunostaining for the anti-S100 antibody, for which it was variable. This fact is related to adipocyte differentiation, where lower amounts of intracytoplasmic lipids translate into lower immunostaining intensity for anti-S100. Histological and immunostaining aspects should be regarded with caution in the diagnosis of pleomorphic liposarcoma, as it is a distinct neoplastic entity, with a complex karyotype and without correlation with the other subtypes.